2011
DOI: 10.1002/adma.201102106
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Interface Structure in Highly Strained YSZ/STO Heterostructures

Abstract: Heterostructures combining transition metal oxides, as compared to other materials, are able to accommodate very large amounts of epitaxial strain without breaking into islands or structural domains. Coherently strained interfaces are an interesting playground for the search of materials with enhanced ion diffusivities, of interest in devices for energy generation and storage. In this work we highlight the importance of the interface structure of highly strained YSZ/STO superlattices in determining an enhancem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…5 The appearance of these space-charge effects in YSZ and its consequences over the oxygen ion conductivity in nanobulk YSZ or thin films has triggered a strong controversy during the last years. [6][7][8][9] While some authors reported an enhancement in the ionic conductivity in samples with nanometer size grains, 10 others have found no changes 11 or even a decrease of the ionic conductivity 12 in samples obtained with different synthesis methods, with different grain sizes, and even with different dopant concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…5 The appearance of these space-charge effects in YSZ and its consequences over the oxygen ion conductivity in nanobulk YSZ or thin films has triggered a strong controversy during the last years. [6][7][8][9] While some authors reported an enhancement in the ionic conductivity in samples with nanometer size grains, 10 others have found no changes 11 or even a decrease of the ionic conductivity 12 in samples obtained with different synthesis methods, with different grain sizes, and even with different dopant concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…However, obtaining single domain YSZ films on STO substrates with orientation other than (001) has proved to be very challenging. For instance, Rivera-Calzada et al 18 studied YSZ(110) films grown on STO(001) using low temperature and high rate deposition conditions, but the films presented structural domains and island growth. Conversely, it has been also reported that YSZ films on the STO(001) are either flat (001)-oriented or rough with tilted (111)-domains depending on the chemical termination, SrO or TiO 2 , of the STO(001) substrates.…”
mentioning
confidence: 99%
“…17 It was proposed that the heteroepitaxy of strained YSZ was possible in spite of the large lattice mismatch of 7% by disorder of the oxygen sublattice at the interface, with oxygen vacancies increasing the oxygen mobility. 17,18 In this context, beyond YSZ(001)/ STO(001) interfaces, the growth of YSZ with dissimilar crystal orientation on top of STO may be instrumental to gain fundamental understanding on oxygen exchange across interfaces, and the role that structural symmetry can have on ionic diffusion. However, obtaining single domain YSZ films on STO substrates with orientation other than (001) has proved to be very challenging.…”
mentioning
confidence: 99%
“…The work presented in this Letter demonstrates that measurements on clamped films may considerably underestimate the piezoelectric coefficients and coupling constants of released structures used in microelectromechanical systems, energy harvesting systems, and microrobots. DOI Strain in epitaxial oxide films has become a universally recognized method for tuning materials properties [1][2][3], enabling novel couplings between magnetic, lattice, and strain behaviors [4][5][6], stabilizing new phases [7] or domain morphologies [8]. Systematic studies of a material's response to strain enable exploration of the fundamental mechanisms responsible for, e.g., the ferroelectric instability [9][10][11][12].…”
mentioning
confidence: 99%